Preparation method of antibiotic adsorption material
By preparing metal-organic framework materials and combining them with activated carbon and urea for activation, the problems of low antibiotic adsorption capacity and poor regenerability in existing technologies have been solved, achieving high-efficiency adsorption and excellent regenerability, making it suitable for antibiotic removal.
Patent Information
- Application Number
- CN202510970060.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-11-21
AI Technical Summary
Existing methods for removing pollutants from water bodies have low adsorption capacity for organic matter or poor regeneration, and are difficult to effectively remove sulfonamide antibiotics.
By preparing metal-organic framework materials, adding activated carbon and activating them with urea, antibiotic adsorbent materials are formed. The synergistic effect of the incorporation of activated carbon and the activation by urea improves the adsorption capacity and regenerability.
It achieves high adsorption capacity and excellent regenerability for antibiotics, significantly improving adsorption capacity and exhibiting excellent regenerability, thus avoiding secondary pollution and reducing costs.
Smart Images

Figure CN120984238A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of antibiotic treatment, in particular to an antibiotic adsorption material preparation method. BACKGROUND
[0002] Since the advent of antibiotics, it has played a huge role in the medical industry, animal husbandry, aquaculture and other industries. In recent years, with the enhancement of people's health consciousness, people have gradually paid attention to the relationship between antibiotics and the environment. Antibiotics can enter the environment through various channels, among which the detection rate of typical antibiotics sulfonamides in water bodies is higher. Sulfonamides are stable in structure and difficult to degrade, and can coexist with the environment for a long time, affecting human health.
[0003] Sulfacetamide is a broad-spectrum antibacterial drug and a typical representative of sulfonamide antibiotics. At present, people have begun to study the removal method of sulfacetamide in the environment to reduce the harmful effects of antibiotics on the human body. The main methods can be divided into two categories: one is biological treatment, which is also a conventional method for removing antibiotics in water and has been adopted by many countries. This method has poor removal effect on dissolved organic matter in water and is difficult to degrade persistent organic pollutants. The second is biochemical method, such as biological contact oxidation method, activated carbon method, ion exchange, advanced oxidation and other methods. Contact oxidation method can efficiently remove pollutants in water, but the adsorption amount of dissolved degradable organic matter is not high. Adsorption method is widely used in wastewater, such as adsorbing tetracycline in wastewater, using SiO2 and activated carbon with similar pore size to adsorb tetracycline in the environment, and obtaining a high removal rate. However, the regeneration of SiO2 and activated carbon is poor. Therefore, it has become a technical problem for those skilled in the art to provide an adsorption material with excellent adsorption capacity and regeneration. SUMMARY
[0004] In view of the deficiencies of the prior art, the present application provides an antibiotic adsorption material preparation method, which solves the technical problems of low adsorption amount of organic matter or poor regeneration of the existing methods for removing pollutants in water.
[0005] To achieve the above object, the technical scheme is as follows:
[0006] The present application provides an antibiotic adsorption material preparation method, comprising the following steps:
[0007] Nine water chromium nitrate, terephthalic acid, deionized water and hydrofluoric acid are reacted to obtain a metal organic framework, which is first doped with activated carbon and then activated with urea to obtain an antibiotic adsorption material.
[0008] The method above first obtains a metal organic framework by reacting chromium nitrate nine hydrate, terephthalic acid, deionized water and hydrofluoric acid, and then prepares an antibiotic adsorption material by incorporating active carbon and activating with urea. The incorporation of active carbon and the activation with urea have a synergistic effect on improving the adsorption capacity of the adsorption material to antibiotics and the regenerability. Therefore, the prepared antibiotic adsorption material has a large adsorption capacity to antibiotics and excellent regenerability.
[0009] Preferably, a method for preparing an antibiotic adsorption material comprises the following steps:
[0010] S1, placing chromium nitrate nine hydrate, terephthalic acid, deionized water and hydrofluoric acid in a reaction container, and reacting under vacuum at a temperature of 493-510 K for 8-10 h to obtain a mixed solution containing a metal organic framework; the pore size distribution of the metal organic framework is 1-3 nm;
[0011] S2, adding active carbon to the mixed solution and mixing uniformly, and performing a constant-temperature hydrothermal synthesis reaction at 493-510 K for 8-10 h, centrifuging to collect dark green precipitate, and washing the dark green precipitate until the supernatant is clear to obtain dark green carbon-incorporated metal organic framework;
[0012] S3, activating the dark green carbon-incorporated metal organic framework with urea, and washing to obtain an antibiotic adsorption material.
[0013] The reaction conditions of steps S2 and S3 are controlled within a suitable range, so that the incorporation of active carbon and the activation with urea have a synergistic effect on improving the adsorption capacity of the adsorption material to antibiotics and the regenerability.
[0014] The prepared metal organic framework has an infinite extension characteristic, the metal ligand structure has the functions of metal nodes and bridging organic ligands, and has an adjustable porous structure with an average pore size of 2.23 nm, so that the active carbon is uniformly filled into the metal organic framework and adsorbed into the large pores of the metal organic framework, a high specific surface area and active sites are achieved, and a large adsorption capacity to antibiotics is achieved.
[0015] Preferably, in step S1, the mass ratio of the chromium nitrate nine hydrate to the terephthalic acid is 1:1.
[0016] Preferably, in step S1, the addition amount of the hydrofluoric acid is 0.5 ml / L.
[0017] Preferably, in step S1, the mass concentration of the hydrofluoric acid is 40%.
[0018] Preferably, in step S2, the addition amount of the active carbon is 10 g.
[0019] The addition amount of activated carbon is controlled in a proper range, and the activated carbon is uniformly filled into the metal organic framework and adsorbed into the large pores of the metal organic framework, so that a high specific surface area and active sites are achieved, and a large adsorption amount of antibiotics is achieved.
[0020] The pore size of the activated carbon is 2-50 nm, and the specific surface area is 500-1000 m 2 / g.
[0021] The pore size distribution of the metal organic framework is 1-3 nm, and the pore size and specific surface area of the activated carbon are controlled in a proper range, so that the activated carbon is uniformly filled into the metal organic framework and adsorbed into the large pores of the metal organic framework, so that a high specific surface area and active sites are achieved, and a large adsorption amount of antibiotics is achieved.
[0022] Preferably, in step S2, the dark green precipitate is sequentially washed with deionized water, dimethylformamide and ethanol until the supernatant is clear.
[0023] Preferably, in step S3, the addition amount of urea is 0.6 g.
[0024] The addition amount of urea is controlled in a proper range, so that specific active sites are generated during the urea activation process.
[0025] Preferably, in step S3, the activation condition is that the dark green carbon is activated by using urea to incorporate the metal organic framework, that is, the urea and the dark green precipitate are placed in a round-bottom flask for reflux for 12 hours to complete the grafting. BRIEF DESCRIPTION OF DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed in the embodiment or prior art description will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor.
[0027] Figure 1 is a preparation method flowchart of the antibiotic adsorption material of Example 1.
[0028] Figure 2 is an XRD pattern of the adsorption material Urea-MIL-101(Cr)@AC-1 prepared in Example 1 and the first regenerated adsorbent of the adsorption material prepared in Example 1. DETAILED DESCRIPTION
[0029] In order to make the purposes, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0030] In order to better understand the above technical solutions, the above technical solutions will be described in detail below in combination with the drawings in the specification and specific embodiments.
[0031] I. Preparation method
[0032] Embodiment 1
[0033] The present embodiment provides a preparation method of an antibiotic adsorption material, as shown in the following formula: Figure 1 The preparation method comprises the following steps:
[0034] S1, 0.01 mol of chromium nitrate nonahydrate, 0.01 mol of terephthalic acid, 50 ml / L of deionized water, and 0.5 ml / L of 40% hydrofluoric acid are placed in a reaction kettle with a polytetrafluoroethylene inner liner; it is placed in a vacuum oven, the temperature is 493 K, and the reaction is carried out for 8 h to obtain a mixed solution containing the main structure MIL-101(Cr).
[0035] S2, 10 g of activated carbon with a pore size of 2-25 nm and a specific surface area of 500-600 m 2 / g is added to the mixed solution of S1 and mixed uniformly, and a constant temperature hydrothermal synthesis reaction is carried out at 493 K for 8 h, then the dark green precipitate is collected by centrifugation, and the dark green precipitate is washed with deionized water, dimethylformamide and ethanol in sequence until the supernatant is clear, and the activated carbon is incorporated into the MIL-101(Cr) framework to obtain dark green MIL-101(Cr)@AC.
[0036] S3, 0.6 g of urea is added to activate the dark green MIL-101(Cr)@AC, that is, the urea and the dark green precipitate are placed in a round-bottom flask and refluxed for 12 hours to complete the grafting. After functionalization, it is washed clean to obtain the adsorption material Urea-MIL-101(Cr)@AC-1.
[0037] The C content and N content of MIL-101(Cr), MIL-101(Cr)@AC and Urea-MIL-101(Cr)@AC-1 are tested by using an elemental analyzer, and the results are shown in Table 1.
[0038] Table 1
[0039]
[0040] From Table 1, it can be seen that the carbon content of MIL-101(Cr) is 31.42% according to the elemental analysis, and after adding activated carbon, the carbon content of MIL-101(Cr)@AC increases to 38.21%, indicating that activated carbon enters the material by reaction, and after adding urea, the nitrogen content of Urea-MIL-101(Cr)@AC-1 changes from 13.52% to 20.13%. The increase of N content confirms that MIL-101(Cr)@AC introduces nitrogen elements by urea modification.
[0041] Example 2
[0042] The embodiment provides a preparation method of an antibiotic adsorption material, comprising the following steps:
[0043] S1, 0.01 mol of chromium nitrate, 0.01 mol of terephthalic acid, 50 ml / L of deionized water, 0.5 ml / L of 40% hydrofluoric acid are placed in a reaction kettle with a polytetrafluoroethylene inner container; it is placed in a vacuum oven, the temperature is 493 K, and the reaction is carried out for 8 h, to obtain a mixed solution containing a main structure MIL-101(Cr).
[0044] S2, 10g of activated carbon with a pore size of 25-40nm and a specific surface area of 600-800m 2 / g is added to the mixed solution of S1 and mixed uniformly, 493 K constant temperature hydrothermal synthesis reaction is carried out for 8 h, then the dark green precipitate is collected by centrifugation, and the dark green precipitate is washed with deionized water, dimethylformamide and ethanol in sequence until the upper liquid is clear, and the activated carbon is incorporated into the MIL-101(Cr) framework to obtain dark green MIL-101(Cr)@AC.
[0045] S3, 0.6g of urea is added to the dark green MIL-101(Cr)@AC for grafting activation, after functionalization, washing is carried out to obtain an adsorption material Urea-MIL-101(Cr)@AC-2.
[0046] Example 3
[0047] The embodiment provides a preparation method of an antibiotic adsorption material, comprising the following steps:
[0048] S1, 0.01 mol of chromium nitrate, 0.01 mol of terephthalic acid, 50 ml / L of deionized water, 0.5 ml / L of 40% hydrofluoric acid are placed in a reaction kettle with a polytetrafluoroethylene inner container; it is placed in a vacuum oven, the temperature is 493 K, and the reaction is carried out for 8 h, to obtain a mixed solution containing a main structure MIL-101(Cr).
[0049] S2, 10g of activated carbon with a pore size of 25-40nm and a specific surface area of 600-800m2 / g activated carbon and mixed evenly, 493 K constant temperature hydrothermal synthesis reaction for 8 h, then centrifugal collection of dark green precipitate, and then use deionized water, dimethylformamide and ethanol to clean the dark green precipitate until the supernatant is clear, and the activated carbon is incorporated into the MIL-101(Cr) framework to obtain dark green MIL-101(Cr)@AC.
[0050] S3, 0.6 g of urea is added to the dark green MIL-101(Cr)@AC for grafting activation, and after functionalization, it is washed clean to obtain the adsorbent material Urea-MIL-101(Cr)@AC-3.
[0051] Comparative Example 1
[0052] The difference between this comparative example and Example 1 is that step S3 is not included, and the other steps are the same as Example 1. The prepared adsorbent material is dark green MIL-101(Cr)@AC-1.
[0053] Comparative Example 2
[0054] The difference between this comparative example and Example 1 is that step S2 is not included, and the other steps are the same as Example 1. The prepared adsorbent material is Urea-MIL-101(Cr).
[0055] Comparative Example 3
[0056] The difference between this comparative example and Example 1 is that steps S2 and S3 are not included, and the other steps are the same as Example 1. The prepared adsorbent material is MIL-101(Cr)-1.
[0057] II. Test method
[0058] The adsorption capacity and regeneration performance of the adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3 for antibiotics were tested. The test method is as follows:
[0059] First antibiotic adsorption capacity: using a plastic centrifuge tube, 50 ml of 120 mg / L sulfacetamide solution was measured (the preparation method of the sulfacetamide solution is to weigh a certain amount of sulfacetamide into a beaker, add a certain amount of distilled water, and assist ultrasonic dissolution until the drug is completely dissolved, then transfer to a 1L volumetric flask, prepare the required concentration of stock solution, and store in a refrigerator), 10 mg of the adsorbent material prepared in each example or comparative example was added, and it was placed in a constant magnetic stirrer at 298 K. The pH was adjusted to 2-10, and after reaching adsorption equilibrium, the residual antibiotic content in the water was determined by ultraviolet spectrophotometry, and the adsorbent material was recovered by filtration.
[0060] The first antibiotic adsorption capacity of each example or comparative example adsorbent material was calculated according to formula (1).
[0061] First antibiotic adsorption capacity qt = (C0-Ct) / m (1) t
[0062] In formula (1), q represents the adsorption capacity (unit: mg / g), C0represents the initial concentration of the antibiotic (unit: mg / L), Ctrepresents the antibiotic concentration (unit: mg / L) at time t. t t
[0063] The recovered adsorption material was immersed in a 99% methanol solution, and the adsorbed sulfacetamide was separated for 24 hours. The separated adsorption material was washed with methanol and placed in a 60°C oven for drying to obtain the first regenerated adsorbent.
[0064] The above steps of adsorbing the target pollutant and recovering the adsorption material were repeated using the first regenerated adsorbent to obtain the second regenerated adsorbent, and the antibiotic adsorption rate of the first regenerated adsorbent was calculated according to formula (2). In the same way, the Nth regenerated adsorbent was obtained, and the antibiotic adsorption rate of the (N-1) th regenerated adsorbent was calculated. Until the antibiotic adsorption rate of the (N-1) th regenerated adsorbent is < 50%, the Nth regenerated adsorbent is stopped.
[0065] The antibiotic adsorption rate of the Nth regenerated adsorbent is a = q / m (2)
[0066] In formula (2), q represents the mass of the adsorbate on the adsorbent, and m represents the mass of the adsorbent.
[0067] The structures of the adsorption material prepared in Example 1 and the first regenerated adsorbent of the adsorption material prepared in Example 1 were characterized by XRD, respectively, as shown in Figure 2 .
[0068] The SiO2 with a pore size of 2 nm and the 2 nm activated carbon were used to replace the adsorption material Urea-MIL-101(Cr)@AC-1 prepared in Example 1 to adsorb the target pollutant using the above adsorption target pollutant steps, and the recovered regenerated SiO2 and activated carbon were used to adsorb the target pollutant again. The first antibiotic adsorption amount of the target pollutant and the antibiotic adsorption rate of the Nth regenerated adsorbent are shown in Table 2. Among them, the method for recovering the SiO2 adsorption material is a physical recovery method; the method for recovering the activated carbon adsorption material is a thermal regeneration method; the SiO2 and the activated carbon are purchased from Shanghai Huxi Company as analytical pure reagent materials.
[0069] III. Test Results
[0070] The performance test results of the adsorption materials of Examples 1-3 and Comparative Examples 1-3, SiO2, and activated carbon are shown in Table 2.
[0071] Table 2
[0072]
[0073] As shown in Table 2, the initial antibiotic adsorption capacity of the adsorbents prepared in Examples 1-3 was 30-38 mg / g, while that of the adsorbents prepared in Comparative Examples 1-3 was only 14.5-20 mg / g. This indicates that without steps S2 and / or S3, the adsorbents could not achieve a high initial antibiotic adsorption capacity. Therefore, steps S2 and S3 have a synergistic effect in improving the antibiotic adsorption capacity of the adsorbents. Similarly, comparing the antibiotic adsorption rates of the adsorbents in Examples 1-3 and Comparative Examples 1-3 after Nth regeneration shows that without steps S2 and / or S3, the adsorbents could not achieve optimal regenerability. Therefore, steps S2 and S3 have a synergistic effect in improving the regenerability of the adsorbents.
[0074] In addition, as shown in Table 2, the initial antibiotic adsorption capacity of the adsorbent material prepared in this application is comparable to that of traditional adsorbents SiO2 and activated carbon, but its renewability is superior to that of SiO2 and activated carbon. Therefore, it does not generate secondary pollution, is environmentally friendly, and reduces costs.
[0075] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0077] The present invention has been illustrated with the above embodiments to describe the detailed process flow of the present invention. However, the present invention is not limited to the above detailed process flow, that is, it does not mean that the present invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an antibiotic adsorbent material, characterized in that, Includes the following steps: A metal-organic framework is obtained by reacting chromium nitrate nonahydrate, terephthalic acid, deionized water, and hydrofluoric acid. The metal-organic framework is first incorporated with activated carbon and then activated with urea to obtain an antibiotic adsorbent material.
2. The method for preparing the antibiotic adsorbent material as described in claim 1, characterized in that, Includes the following steps: S1. Chromium nitrate nonahydrate, terephthalic acid, deionized water, and hydrofluoric acid are placed in a reaction vessel and reacted under vacuum at a temperature of 493-510K for 8-10 hours to obtain a mixture containing a metal-organic framework. S2. Add activated carbon to the mixture and mix evenly. Perform hydrothermal synthesis reaction at a constant temperature of 493-510K for 8-10 hours. Collect the dark green precipitate by centrifugation and wash the dark green precipitate until the upper liquid is clear to obtain dark green carbon incorporated into the metal-organic framework. S3. The dark green carbon is activated by incorporating a metal-organic framework with urea and then washed to obtain an antibiotic adsorbent material.
3. The method for preparing antibiotic adsorbent material as described in claim 2, characterized in that, In step S1, the molar ratio of chromium nitrate nonahydrate to terephthalic acid is 1:
1.
4. The method for preparing the antibiotic adsorbent material as described in claim 2, characterized in that, In step S1, the amount of hydrofluoric acid added is 0.5 ml / L.
5. The method for preparing antibiotic adsorbent material as described in claim 2, characterized in that, Step S1, the mass concentration of the hydrofluoric acid is 40%.
6. The method for preparing the antibiotic adsorbent material according to claim 2, characterized in that, Step S2, the activated carbon has a pore size of 2-50 nm and a specific surface area of 500-1000 m². 2 / g.
7. The method for preparing the antibiotic adsorbent material according to claim 2, characterized in that, Step S2: Wash the dark green precipitate sequentially with deionized water, dimethylformamide and ethanol until the supernatant is clear.
8. The method for preparing the antibiotic adsorbent material as described in claim 2, characterized in that, Step S3, the activation process is to place urea and dark green precipitate in a round-bottom flask and reflux for 12 hours.